Pengaruh Inventarisasi, Kompetensi Aparatur, dan Pengendalian Internal terhadap Optimalisasi Pengelolaan Barang Milik Daerah - Listiani Listiani; Henri Agustin (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to examine the effect of inventory, the competence of apparatus, and internal control systems on optimizing the management of regional property. The population of this research is all Regional Apparatus Organizations in Pelalawan Regency. The sampling technique used was total sampling, where as many as 27 Regional Apparatus Organizations in Pelalawan Regency were used as research samples. From each Regional Apparatus Organizations, 4 people were taken as respondents, consisting of 1 Head of General Subdivision, 1 Head of Finance Subdivision, and 2 Managers of Goods, so that a total of 108 respondents were obtained. The data was collected by distributing questionnaires directly to the respondents. This research uses quantitative method and the data were processed using multiple linear regression analysis with the help of the IBM SPSS Statistic version 22. The results of statistical tests stated that the inventory had a positive and significant effect on the optimization of the management of regional property. Meanwhile, the competence of the apparatus and the internal control system has no significant effect on the optimization of the management of regional property.